Lappula monocarpa, a new synonym of Lappula tenuis (Boraginaceae) - Dan-Hui Liu (PhytoKeys)
Lappula monocarpa is currently the sole described species within the genus Lappula characterized by the development of a single nutlet per fruit. However, since its initial publication, no additional specimens of L. monocarpa have been collected. Critical examination of type specimens, combined with field surveys and newly collected material, reveals that the diagnostic trait of L. monocarpa—the presence of a single nutlet per fruit—is not consistently observed and likely represents an aberrant specimen. Moreover, all other morphological characteristics of L. monocarpa, including indumentum, corolla, and nutlet features, align fully with those of L. tenuis. Based on this evidence, L. monocarpa is herein reduced to a synonym of L. tenuis.